Identification in synovial fluid of a new potential pathogenic player in arthropathies. Issue 12 (June 2022) - Scanu, Anna; Lorenzin, Mariagrazia; Luisetto, Roberto; Galozzi, Paola; Ortolan, Augusta; Oliviero, Francesca; Doria, Andrea; Ramonda, Roberta
STING (stimulator of interferon genes) has been recognized as an important signaling molecule in the innate immune response to cytosolic nucleic acids. Although it has been proposed that STING signaling pathway may play a pathogenic role in developing autoimmune and autoinflammatory diseases, its involvement in rheumatic disease processes remains to be elucidated. Here, we evaluated STING protein levels, expression and relationship with inflammatory parameters in synovial fluid (SF) of patients with psoriatic arthritis (PsA), rheumatoid arthritis (RA), gout, calcium pyrophosphate crystal-induced arthritis (CPP-IA), osteoarthritis (OA), and OA with CPP crystals (OA + CPP). The correlation with its negative regulator, nuclear factor erythroid 2-related factor 2 (Nrf2), was also investigated. SFs from 72 patients were analyzed for white blood cell (WBC) count, polymorphonuclear cell percentage (PMN%), and IL-1β, IL-6, IL-8, extra- and intracellular STING levels. STING and Nrf2 expression was also determined. WBC count and PMN% were greater in SF from inflammatory arthritis, while they were lower in OA groups. RA and gouty SFs have the highest levels of IL-1β, IL-8, and IL-6; while OA and OA + CPP showed the lowest concentrations. Gout and RA had the highest intracellular STING levels, while extracellular STING was greater in CPP-IA and OA SFs. STING was not detectable in PsA. STING mRNA was lower in PsA than other arthritides. Nrf2 mRNA was not detectable in OA. This study determines the presence of STING in SF of different arthritides, except for PsA, and suggests that it may be involved in pathogenesis and progression of arthropathies.